Differences in Vastus Medialis and Vastus Lateralis Activity during Squating at Various Toe-Out Ankle Angles - Kim, Chihwan; Cho, Sunghak (Journal of International Academy of Physical Therapy Research, 2024)
Background: Squats are often used to strengthen the quadriceps femoris, but they are affected by lower extremity posture. Objectives: The study of this was to investigate the effect on the muscle activity of the vastus medialis and the vastus lateralis according to the ankle angle, during squat exercise. Design: Quasi-Experimental research. Methods: Thirty healthy adult males participated in the study and the subjects measured the vastus medialis muscle and the vastus lateralis muscle and measured the maximum electromyogram. The subjects performed one squat at ankle angles of toe out 0˚, toe out 20˚, and toe out 40˚, then rested for 2 minutes and repeated 3 sets. Data analysis was performed using the repeated measures analysis of variance and paired t-test for window program. The significance level for statistical treatment was set at .05. Results: There was a statistically significant difference in the vastus medialis and the vastus lateralis in the ankle angles of toe out 0˚, toe out 20˚, and toe out 40˚during squat (P<.05). The muscle activity of the vastus medialis and vastus lateralis showed the highest at the ankle angle toe out 20˚, and the vastus medialis showed a statistically significant increase at toe out 0˚ than at toe out 40˚ (P<.05). In vastus lateralis, toe out 40˚ increased statistically more than toe out 0˚(P<.05). Conclusion: In the early stage of rehabilitation for patients with knee pain, strengthening the vastus medialis muscle at toe out 0˚and performing squat exercise at toe out 20˚ in the later period will be helpful. However, if you exercise at toe out 40˚ beyond toe out 20˚, the vastus lateralis muscle becomes dominant, so it will not be helpful during squat exercise.